Prevention of Self‐Quenching in Fluorescent Silica Nanoparticles by Efficient Energy Transfer1. Issue 23 (24th April 2013) - Genovese, Damiano; Bonacchi, Sara; Juris, Riccardo; Montalti, Marco; Prodi, Luca; Rampazzo, Enrico; Zaccheroni, Nelsi
<x xml:space="preserve">Abstract</x> Stars that shine bright: A high local dye concentration in doped silica‐based core–shell nanoparticles causes self‐quenching and spectral broadening (top images). This phenomenon jeopardizes the potential advantages of heavily doped systems. Förster resonance energy transfer (FRET) to an acceptor co‐included in the silica led to ultrabright nanoparticles (bottom images) with a preselected narrow‐band emission and a pseudo‐Stokes shift of 129 nm.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>